2019
DOI: 10.4103/ijn.ijn_334_17
|View full text |Cite
|
Sign up to set email alerts
|

Collapsing glomerulopathy superimposed on diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is characterized by gradually progressive renal failure and proteinuria. Various types of nondiabetic kidney diseases may superimpose on DN, and affect the natural course, prognosis, and management. Collapsing glomerulopathy (CG) is a form of glomerular proliferative injury, characterized by rapid progression and associated with poor prognosis. CG may be idiopathic or secondary to other causes, and it has also been described with other forms of glomerular diseases. The association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Additionally, HE, PAS, and Masson staining showed that the degree of renal pathological injury and fibrous hyperplasia improved significantly in the model group with the administration of DMix ( Figure 5 ). DN is characterized by proteinuria and glomerular sclerosis [ 23 , 24 ], and our results indicate that DMix not only reduces urinary protein levels but also reduces renal fibrosis, suggesting that DMix effectively prevents the development of DN.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, HE, PAS, and Masson staining showed that the degree of renal pathological injury and fibrous hyperplasia improved significantly in the model group with the administration of DMix ( Figure 5 ). DN is characterized by proteinuria and glomerular sclerosis [ 23 , 24 ], and our results indicate that DMix not only reduces urinary protein levels but also reduces renal fibrosis, suggesting that DMix effectively prevents the development of DN.…”
Section: Discussionmentioning
confidence: 71%